NILAI BUDAYA PALI DAYAK NGAJU (CULTURAL VALUE AS REPRESENTED IN THE PALI OF DAYAK NGAJU) - Bayu Sugara (Universitas Lambung Mangkurat, 2021)
Abstract Cultural Values as Represented in the Pali of Dayak Ngaju Community. This research aims to (1) describe the cultural values as represented in the pemali belonging to the Dayak Ngaju community towards nature, (2) describe the cultural values as represented in the pemali belonging to the Dayak Ngaju community towards the human interaction, (3) describe the cultural values as represented in the pemali belonging to the Dayak Ngaju community towards the spiritual performance. This research uses (1) recording techniques, both audio and audiovisual, (2) recording, (3) in-depth interviews, (4) literature study and documentation analysis.The results of the study show that the representation of cultural values of the pemali of the Dayak Ngaju Community in relation to nature includes: (1) the prohibition of not asking for permission when going to farming; (2) prohibition to kill animals carelessly while hunting; (3) prohibition of burning forest carelessly; (4) mapas lewu 'cleaning the village'; (5) manyanggar (‘someone should excuse me from the forest rangers’ otherwise it can cause danger and take victims); (6) prohibition of making images (statues) of animals carelessly in a forest inhabited by supernatural beings. The representations of cultural values of the pemali of the Dayak Ngaju Community concerning the human interactions, including: (1) prohibitions against marrying in the wrong lineage or the same lineage; (2) prohibition to take or interfere with the rights of others; (3) prohibition of entering another's house without permission; (4) prohibition to pick up the fallen fruit without the owner's consent; and (5) prohibition to swear/curse children carelessly.The representations of cultural values of the pemali of the Dayak Ngaju Community to the spiritual performance, including (1) the obligation to provide food to village guards (Pakanan Patahu); (2) the duty to always remember the Almighty while earning a living; (3) prohibition to laugh at broomstick; (4) prohibition of picking sawang leaves in front of the sangar patahu. Key words: value, representation, multiplier, dayak ngajuAbstrak Nilai Budaya Pali Dayak Ngaju. Tujuan Penelitian ini adalah (1) mendeskripsikan representasi nilai budaya pemali masyarakat Dayak Ngaju terhadap alam. (2) Mendeskripsikan representasi nilai budaya pemali masyarakat Dayak Ngaju terhadap interaksi sesama manusia. (3) Mendeskripsikan representasi nilai budaya pemali masyarakat Dayak Ngaju terhadap kemampuan spritual.Metode atau teknik pengumpulan data dalam penelitian ini menggunakan: (1) teknik perekaman, baik audio maupun audiovisual, (2) pencatatan, (3) wawancara yang mendalam, (4) studi kepustakaan dan analisis dokumentasi.Hasil penelitian menunjukan representasi nilai budaya pemali masyarakat Dayak Ngaju yang berhubungan dengan alam meliputi: (1) larangan tidak permisi jika hendak berladang; (2) tidak boleh membunuh binatang sembarangan saat berburu; (3) tidak boleh membakar hutan sembarangan; (4) mapas lewu ‘membersihkan Jurnal Bahasa, Sastra dan Pembelajarannya Vol 11, No 2, Oktober 2021 ISSN 2089-0117 (Print) Page 286 - 300 ISSN 2580-5932 (Online) Sugara,/ Jurnal Bahasa, Sastra dan Pembelajarannya 11 (2) 2021, 286 - 300 Jurnal Bahasa, Sastra dan Pembelajarannya ǀ 287 kampung’; (5) manyanggar ‘harus permisi dengan penjaga-penjaga hutan’ kalau tidak dapat menimbulkan bahaya dan memakan korban; (6) jangan membuat gambar (patung) hewan sembarangan di dalam hutan yang ada penunggunya.Representasi nilai budaya pemali Dayak Ngaju yang berhubungan dengan interaksi sesama manusia meliputi: (1) Tidak boleh menikah salah silsilah atau dalam satu garis keturunan yang sama; (2) tidak boleh mengambil atau mengganggu hak orang lain; (3) tidak boleh masuk rumah orang lain tanpa permisi; (4) tidak boleh mangambil buah yang jatuh tanpa izin pemiliknya; dan (5) tidak boleh menyumpahi/mengutuk anak sembarangan.Representasi nilai budaya pemali Dayak Ngaju yang berhubungan dengan kemampuan spritual adalah (1) tidak boleh tidak memberi makanan untuk penjaga kampung (Pakanan Patahu); (2) tidak boleh lupa dengan Sang Maha Kuasa saat mencari nafkah; (3) tidak boleh menertawakan sapundu; (4) tidak boleh memetik daun sawang di depan sangar patahu. Kata-kata kunci: nilai, representasi, pali, dayak ngaju